Analysis of the Role of Experience, Ability and Motivation on Employee Performance - Ella Anastasya Sinambela; Ernawati Ernawati (metromedia.education, 2021)
Human resource planning is directed so that each employee is able to provide work results in accordance with the standards set by the company. The company's ability to achieve goals is also determined by the work of employees to carry out their duties. This associative research aims to determine the effect of experience, ability, and work motivation on employee performance. The population of this study are employees of a distributor company in the city of Surabaya. The study took samples from all members of the population, amounting to 77 respondents. This study uses multiple linear regression data analysis techniques. From the results of data analysis, it was found that experience had a significant effect on employee performance. Work ability has a significant effect on employee performance. Motivation has a significant effect on employee performance. Experience, ability, and motivation simultaneously have a significant effect on employee performance